At the heart of change: Differences in young offenders’ HRV patterns after the delivery of the PSYCHOPATHY.COMP program - Sousa, Rúben; Ribeiro da Silva, Diana; Petrocchi, Nicola; Gilbert, Paul; Rijo, Daniel (Frontiers in Psychiatry, 2023)
Literature has pointed the need for intervention programs specifically tailored to target the treatment needs of young offenders, as well as the need to test the efficacy of such programs through physiological indexes of emotion regulation (e.g., heart rate variability; HRV), complementing self-reports typically used as outcome measures. The PSYCHOPATHY.COMP is a 20-session individual intervention program based on Compassion Focused Therapy aiming to reduce psychopathic traits and disruptive behavior among young offenders through the development of a compassionate motivation, while stimulating the soothing system as a strategy to improve emotion regulation. Previous research with young offenders has shown decreases in vagally mediated HRV (vmHRV) when the soothing system is activated. This physiological pattern seems to mirror threat-like responses that contrast with relaxed states. To test the efficacy of the PSYCHOPATHY.COMP, a clinical trial was implemented encompassing a treatment (n = 56) and a control group (n = 53). Treatment participants attended the PSYCHOPATHY.COMP, while controls received the Treatment As Usual (TAU) delivered in Portuguese juvenile detention facilities. HRV data was collected throughout a standardized procedure (encompassing resting, reactivity and recovery phases) specifically designed to trigger the soothing system. Participants were assessed at pre-treatment, post-treatment and 6-months follow-up. Although treatment participants continued to process the soothing system as unpleasant (with decreased vmHRV), they seem to become able to adaptively recover from the stimuli without avoiding it or resorting to maladaptive coping strategies. The physiological pattern was in line with participants’ decreases in difficulties in emotion regulation across the assessment periods. In contrast, controls seemed to have actively employed coping strategies associated with increases in vmHRV not only when the soothing system was triggered, but also when recovering from the stimuli. Congruently, for controls, increases in difficulties in emotion regulation were found, with increases in the lack of emotional clarity across the assessment periods. Findings offer new evidence for the efficacy of the PSYCHOPATHY.COMP program in improving emotion regulation in young offenders, assessed through both self-report and physiological measures. Additionally, findings support the assessment of the autonomic balance as a treatment efficacy index in future research, targeting the rehabilitation of these youth.